Chromatin compaction during confined cell migration induces and reshapes nuclear condensates - Jessica Z. Zhao; Jing Xia; Clifford P. Brangwynne (Nature Communications)
Abstract Cell migration through small constrictions during cancer metastasis requires significant deformation of the nucleus, with associated mechanical stress on the nuclear lamina and chromatin. However, how mechanical deformation impacts various subnuclear structures, including protein and nucleic acid-rich biomolecular condensates, is largely unknown. Here, we find that cell migration through confined spaces gives rise to mechanical deformations of the chromatin network, which cause embedded nuclear condensates, including nucleoli and nuclear speckles, to deform and coalesce. Chromatin deformations exhibit differential behavior in the advancing vs. trailing region of the nucleus, with the trailing half being more permissive for de novo condensate formation. We show that this results from increased chromatin heterogeneity, which gives rise to a shift in the binodal phase boundary. Taken together, our findings show how chromatin deformation impacts condensate assembly and properties, which can potentially contribute to cellular mechanosensing.